Preserving the Paser Adang Language and Teaching English through a Participatory Approach at SDN 008 Long Gelang Village: Pelestarian Bahasa Paser Adang dan Pembelajaran Bahasa Inggris Melalui Pendekatan Partisipatif di SDN 008 Desa Long Gelang - Julianingsih; Ine Marianti; Siti Fatimah Putri; Cindy Adesti Aprelia; Riski Brahmana; Tasya Dwi Septiani; Wilmar Ghatan Al-Rifqi; Abdul Mahada; Rosalina Deran; Nur Aiman Amisyah; Mariyah (ANDIL Mulawarman Journal of Community Engagement, 2026)
The declining use of the Paser Adang language among younger generations indicates an increasing risk of local language endangerment, while limited mastery of basic English among elementary school students remains a challenge in responding to globalization. These issues underscore the need for a community service model that integrates local language preservation with early foreign language instruction. This program was implemented at SDN 008 Long Gelang using a participatory approach. Learning activities were designed to be interactive and culturally contextualized through educational games, songs, folk tales, and group-based tasks that linked local culture with basic English learning. The participants were elementary school students who actively engaged in all stages of the program. The results show increased student interest, participation, and ability to use the Paser Adang language in simple communicative contexts, with an achievement rate of 65,00%. Improvements were also observed in basic English vocabulary and expressions, with 35.71% of students demonstrating fluent use of basic English. The participatory approach effectively promoted active engagement and created a meaningful and enjoyable learning environment. This program offers a practical community service model that integrates local language preservation and foreign language learning simultaneously. Collaboration among schools, local communities, and higher education institutions is essential for ensuring program sustainability while strengthening local cultural identity and developing global competence.